Development of UKM-SID Teaching Module for Space Science Education - Mardina, Abdullah; Badariah, Bais; Alina Marie, Hasbi; Rosadah, Abd Majid; Baharudin, Yatim; Mohd Alauddin, Mohd Ali; Siti Aminah, Bahari; Noridawaty, Mat Daud; Mohd Hezri, Mokhtar; Ahmad Faizal, Mohd Zain; Mhd Fairos, Asillam (Elsevier Ltd., 2013)
This paper highlights the development of UKM-SID teaching module for solar flare detection utilizing VLF technique. This module consists of three segments namely, the antena development, preamplifier and data logger. It was introduced in selected high schools in Selangor, Malaysia, where students need to build the antenna, assemble the preamplifier and analyze the data. They were also required to keep a log book of their activities. With the aid of the teaching module, the students gained hands-on experience in carrying out a team project and indirectly enhance their knowledge in space science.